Assessment of Seroconversion to SARS-CoV-2 in a Cohort of Pediatric Kidney Transplant Recipients - Nailescu, Corina; Khalid, Myda; Wilson, Amy C.; Amanat, Fatima; Arregui, Samuel; Canas, Jorge; Hooks, Jenaya; Krammer, Florian; Schwaderer, Andrew L.; Hains, David S. (Frontiers in Pediatrics, 2020)
Background: The occurrence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the associated coronavirus disease 2019 (COVID-19) have profoundly affected adult kidney disease patients. In contrast, pediatric solid organ transplant recipients, including pediatric kidney transplant (KT) recipients, do not seem to be at particularly higher risk for SARS-CoV-2 infection or for severe COVID-19 disease. This patient population might be protected by certain mechanisms, such as the immunosuppressive medications with their anti-inflammatory properties or simply being well-versed in self-protection techniques. Assessing SARS-CoV-2 antibody serologies could potentially help understand why this patient population is apparently spared from severe SARS-CoV-2 clinical courses. Objective: To examine SARS-CoV-2 serologic status in a cohort of pediatric KT recipients. Methods: SARS-CoV-2 anti-spike IgG and IgM antibodies were measured by three different methods in pediatric KT recipients coming for routine clinic visits immediately post-confinement in May-June of 2020. The patients were considered seroconverted if SARS-CoV-2 antibodies were positive by 2/3 methods and weak positive/indeterminate if positive by 1/3. Results: 31 patients were evaluated (about 1/3 of our institution’s pediatric KT population). One patient seroconverted, while three were considered weak positive/indeterminate. None were symptomatic and none had nasopharyngeal PCR confirmed SARS-CoV-2 disease. Conclusions: Seroconversion to SARS-CoV-2 was rare in this population and likely reflects the social distancing practiced by these patients. The results will serve as a foundation for a future longitudinal study to evaluate the long-term emergence and persistence of antibodies in this population and may inform studies of response to a future vaccine.